The rare genus Leptofoenus Smith, 1862 (Hymenoptera: Pteromalidae, Leptofoeninae): new records, and aspects of its distribution - Fernandes, Daniell R.R. (2019)
Despite being the largest and most remarkable species of Chalcidoidea, species of Leptofoeninae are very rarely collected. Here, we expand the distribution range extension of the Leptofoenus howardi (Ashmead, 1895) for Rondônia and Minas Gerais, Leptofoenus stephanoides (Roman, 1920) for Rondônia, Espírito Santo and São Paulo and Leptofoenus westwoodi (Ashmead, 1895) for Roraima, Amazonas, Rondônia, Bahia, Minas Gerais, Rio de Janeiro and Rio Grande do Sul.